Realizing Optimal Current Distributions for Radiation Efficiency in Practical Antennas - Kormilainen, Riku; Hannula, Jari Matti; Saarinen, Tapio O.; Lehtovuori, Anu; Viikari, Ville (IEEE, 2020)
Modern antenna design is facing increasing issues with the radiation efficiency, since the space available for antennas is scarce and antennas are fitted into lossy environments. This letter presents a multiport antenna design method with a computationally efficient way to realize the port currents providing the highest radiation efficiency. In this method, an antenna is described with multiple excitation ports in electromagnetic simulations. The measurement results of an example design demonstrate the achieved benefit compared to traditional antenna design.
Keywords: Current; far field; multiport antenna; radiation efficiency